A REDESIGN LAYOUT TO INCREASE PRODUCTIVITY OF A COMPANY - Vincentia Kitriastika; Prianggada Indra Tanaya; Yuki Indrayadi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2013)
This project is conducted in Company X, a passenger cars wheel producing company located in Sunter, North Jakarta. With a view of increasing the productivity of the company, the focus of this project will be redesigned the layout of the factory. The main problem encountered is that the goods are not produced in single location, causing a considerable hindrance in terms of time and distance, and hence efficiency. The redesigning layout process will use SLP method and flow analysis while supported by analysis of assembly line balancing to optimize the layout. Regarding the evaluation process, ARENA software will be used to simulate and identify the bottleneck in the production process, and comparing the layout alternatives to decide the best layout. The best chosen layout according to the simulation and SLP method that supported with flow analysis and assembly line balancing will be used as the master draft layout that will be proposed to Company X.